Teacher Attitudes and Barriers to GeoGebra Adoption in Secondary Mathematics Education - Georgia Vlachoni; Hera Antonopoulou; Zoe Karanikola; Constantinos Halkiopoulos (Emerging Science Journal, 2025)
Objectives: This study investigates GeoGebra implementation patterns and identifies facilitators and barriers to adoption among Greek secondary mathematics teachers using the Technology Acceptance Model (TAM) framework. Methods: A cross-sectional survey of 82 secondary mathematics teachers in Western Greece was conducted during June-July 2023 (87.7% response rate), using a validated questionnaire to assess actual usage, perceived usefulness, ease of use, and attitudes toward implementation across four mathematical domains. Findings: Results revealed an implementation paradox: low actual usage (M = 2.21) despite positive attitudes (M = 3.53) and recognized usefulness (M = 3.42). Domain-specific variation showed moderate Geometry implementation (M = 2.77) versus very low Statistics adoption (M = 1.77). Regression analysis explained 40.1% of the variance in usage through Ease of Use (β = 0.360) and Attitude (β = 0.281). B2-level ICT certification emerged as a critical threshold for implementation success. Novelty: This study introduces the Contextual Implementation Cascade Framework (CICF), which explains multi-level barriers to educational technology adoption and demonstrates that positive attitudes cannot overcome systemic infrastructural and institutional barriers without comprehensive professional development.